ADA activity in the follicular fluid of infertile women with diminished ovarian reserve can act as a predictor of ovarian reserve - İlhan, Gülşah; Bacanakgil, Besim H.; Köse, Ayşe; Atıcı, Ayben; Yalçınkaya, Şener; Ayyıldız, Mevlüde (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Adenosine deaminase (ADA) catalyses the deamination of adenosine to inosine. In the human reproductive tract, the importance of enzymes that affect metabolism of adenosine, particularly ADA, has been emphasized. It is aimed to evaluate the plasma and follicular fluid (FF) activities of total ADA (ADAT) in infertile women and to determine its relation with ovarian reserve markers and in vitro fertilization (IVF) outcomes. Methods: Plasma and FF activities of ADAT were measured in 106 infertile women. Its relation with ovarian reserve markers and IVF outcomes were determined. Results: There was a significant difference in the ADAT activities between plasma and FF of infertile women (p<0.01). The activity of plasma ADAT was higher than FF ADAT in infertile women (p<0.01). The activity of FF ADAT in DOR group was higher than that of the others (p<0.01). In DOR group; the activity of FF ADAT activity had a negative correlation with BMI and a positive correlation with FSH and no relation with IVF outcomes. Conclusions: Increased ADAT activity can lead to reduced adenosine levels, which might be resulted in disturbed fertility process. The activity of FF ADAT activity might be important for fertility work-up. Further studies are needed.